Asakusa's urban space and the incompleteness of the novel – The Scarlet Gang of Asakusa. Issue 1 (2nd January 2018) - Wada, Hirofumi; White, Brian
Abstract: Despite its frequent characterization as a 'cinematic' novel, Kawabata Yasunari's The Scarlet Gang of Asakusa uses linguistic expression's inherently selective nature to create a rich, yet always incomplete, picture of Asakusa in the reader's mind. Drawing both on intertextual references to contemporary accounts of Asakusa and on concrete references to touchstones of the neighborhood, Kawabata created a 'mental map' of Asakusa that would have differed for each reader, similar to characterizations of the neighborhood as a place that always escaped total capture in description. In this, The Scarlet Gang of Asakusa is emblematic not only of Asakusa but of the written form itself.